Penggunaan Media Audio Visual untuk Meningkatkan Minat Memilih Madrasah Aliyah al-Falah Pesanggrahan Jangkar Situbondo - Ahmad Musaddad (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2017)
Audiovisual Media is one of the External Public Relations, which is used to convey messages of the public relations considering Purpose, Audience , Mass Coverage, and Search Audience. In this research , the use of Audiovisual Media is used to convey the Public Relation messages about Madrasah that are not considered equivalent to the school in terms of curriculum and diploma. Selection of Audiovisual Media because the media is interesting and consists of 2 elements which combines elements of sound and image elements (Video). Audiovisual media has advantages among others , Innovative , Interactive, inflicting pleasure, combining text and images, able to visualize abstract material, storage media which is relatively easy, able to bring dangerous objects, and can display that can not be seen directly. This research using action research methods School with a research subject Students in Junior High School of Al – Falah and Primary School 2 Kumbangsari. The subjects have been selected because it is a limited audience with the aim of raising their understanding about Madrasah and increase their interest to choose Madrasah as further studies.